2018
DOI: 10.1080/09540261.2018.1563530
|View full text |Cite
|
Sign up to set email alerts
|

What’s known about implementing co-located paediatric integrated care: a scoping review

Abstract: Several studies have demonstrated clinical benefits of integrated care for a range of child and adolescent mental health outcomes. However, there is a significant gap between the evidence for efficacy of integrated care interventions vs. their implementation in practice. While several studies have examined large-scale implementation of co-located integrated care for adults, much less is known for children. The goal of this scoping review was to understand how co-located mental health interventions targeting ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 105 publications
(263 reference statements)
1
23
0
Order By: Relevance
“…The literature key word search was conducted on articles published from January 2000 -July 2019 according to the original six-stage process (60) and updated modifications (61) for scoping reviews, and placed key words into concept areas (62). These reviews are typically undertaken to examine the extent, range, and nature of research in a topic area and identify gaps in knowledge rather than to examine more specific, narrow topics based on study designs of systematic reviews; both types of reviews use an approach based on concept, target population and health outcomes.…”
Section: Approachmentioning
confidence: 99%
“…The literature key word search was conducted on articles published from January 2000 -July 2019 according to the original six-stage process (60) and updated modifications (61) for scoping reviews, and placed key words into concept areas (62). These reviews are typically undertaken to examine the extent, range, and nature of research in a topic area and identify gaps in knowledge rather than to examine more specific, narrow topics based on study designs of systematic reviews; both types of reviews use an approach based on concept, target population and health outcomes.…”
Section: Approachmentioning
confidence: 99%
“…Thus, it seems that a number of terms regarding organisational and personnel dynamics need to be in place to initiate, develop, trial, and evaluate new models of care. As the Optimus integrated care model moves to a stage of sustainability, new challenges, not unknown in providing paediatric integrated care [19], are likely to arise.…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review found that components facilitating sustainability of integrated behavioural healthcare were: "interprofessional communication and collaboration at all stages of implementation; clear protocols to facilitate intervention delivery; and co-employment of integrated care providers by specialty clinics" [19]. The Optimus integrated care model features the first two of these, whereas co-employment is not the case, although it would certainly be desirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the beginning of this century, very few pediatricians worked in close coordination with mental health professionals. Despite evidence that child/youth integrated care can be effective and practical, 17 , 18 still only about half of US pediatricians consider that they work in practices co-located with a behavioral health professional. 19 Integration continues to face significant barriers, including lack of consensus on how primary care and co-located mental health professionals should share roles, the need for substantial transformation in how practices operate if they are to provide mental health care, 20 financing schemes that do not incentivize treatment in primary care or collaboration with mental health providers, 21 and a lack of mental health practitioners trained to work in primary care settings (especially in linguistically and culturally diverse communities).…”
Section: Introductionmentioning
confidence: 99%